The Molecular Signatures Database Hallmark Gene Set Collection - Liberzon, Arthur; Birger, Chet; Thorvaldsdóttir, Helga; Ghandi, Mahmoud; Mesirov, Jill P.; Tamayo, Pablo (Cell systems, 2015)
The Molecular Signatures Database (MSigDB) is one of the most widely used and comprehensive databases of gene sets for performing gene set enrichment analysis. Since its creation, MSigDB has grown beyond its roots in metabolic disease and cancer to include >10,000 gene sets. These better represent a wider range of biological processes and diseases, but the utility of the database is reduced by increased redundancy across, and heterogeneity within, gene sets. To address this challenge, here we use a combination of automated approaches and expert curation to develop a collection of “hallmark” gene sets as part of MSigDB. Each hallmark in this collection consists of a “refined” gene set, derived from multiple “founder” sets, that conveys a specific biological state or process and displays coherent expression. The hallmarks effectively summarize most of the relevant information of the original founder sets and, by reducing both variation and redundancy, provide more refined and concise inputs for gene set enrichment analysis. [Display omitted] •We generate 50 “hallmark” gene sets from the Molecular Signature Database (MSigDB)•This required a hybrid approach combining computation with manual expert curation•The hallmarks reduce redundancy and produce more robust enrichment analysis results•We plan to move forward with a program to enhance and expand the hallmarks collection Through extensive automated and manual curation, Liberzon et al. provide a refined and concise collection of “hallmark” gene sets from the Molecular Signatures Database for gene set enrichment analysis.